2016
DOI: 10.4103/0301-4738.99837
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum sodium and potassium levels in patients with senile cataract and age-matched individuals without cataract

Abstract: Aim:The study was to analyze mean serum sodium and potassium levels in cataract patients and age-matched individuals without cataract.Methods and Materials:It was a prospective case-control study. Individuals more than 50 years of age who attended our ophthalmic center in the year 2007-2010 were grouped into those having cataract and those without cataract. Mean serum sodium and potassium levels in the cataract groups were calculated and compared with the control group. Statistical software SPSS14 was used for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 5 publications
4
21
0
Order By: Relevance
“…5 The difference in mean potassium between the two groups was statistically insignificant. Authors concluded that diet with high sodium content was a risk factor for senile cataract formation and dietary modifications could possibly reduce the rate of progression of cataract.…”
Section: Discussionmentioning
confidence: 84%
“…5 The difference in mean potassium between the two groups was statistically insignificant. Authors concluded that diet with high sodium content was a risk factor for senile cataract formation and dietary modifications could possibly reduce the rate of progression of cataract.…”
Section: Discussionmentioning
confidence: 84%
“…Our results are matching with various previous studies. 10,11 As we know in lens there is low amount of sodium and high amount of potassium. There is a role of Na + -K + ATP ase pump and capsular permeability of lens, which maintains the balance between Na and K ions, In this way permeability of lens is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the study by Mathur and Pai[1] entitled, “Comparison of serum sodium and potassium levels in patients with senile cataract and age-matched individuals without cataract,” in which the authors showed that higher serum sodium level is associated with increased risk of senile cataract. We believe that the authors should be congratulated for the great work as the results suggested that high sodium intake could be a risk factor of senile cataract, and underlined the importance of low salt diet, which is in accordance with a recent study on a large population in Korea.…”
mentioning
confidence: 99%
“…[1] To prove this postulate, it would be helpful to collect the aqueous humor sample from the cataract patients before surgery and evaluate the correlation between the sodium concentration in aqueous humor and the severity of cataract. Studies using animal models would also be interesting.…”
mentioning
confidence: 99%
See 1 more Smart Citation